Chemokines as prognostic factor in colorectal cancer patients: a systematic review and meta-analysis - Fellhofer-Hofer, Johanna; Franz, Clemens; Vey, Johannes; Kahlert, Christoph; Kalkum, Eva; Mehrabi, Arianeb; Halama, Niels; Probst, Pascal; Klupp, Fee (International journal of molecular sciences, 2024)
Chemokines orchestrate many aspects of tumorigenic processes such as angiogenesis, apoptosis and metastatic spread, and related receptors are expressed on tumor cells as well as on inflammatory cells (e.g., tumor-infiltrating T cells, TILs) in the tumor microenvironment. Expressional changes of chemokines and their receptors in solid cancers are common and well known, especially in affecting colorectal cancer patient outcomes. Therefore, the aim of this current systematic review and meta-analysis was to classify chemokines as a prognostic biomarker in colorectal cancer patients. A systematic literature search was conducted in PubMed, CENTRAL and Web of Science. Information on the chemokine expression of 25 chemokines in colorectal cancer tissue and survival data of the patients were investigated. The hazard ratio of overall survival and disease-free survival with chemokine expression was examined. The risk of bias was analyzed using Quality in Prognosis Studies. Random effects meta-analysis was performed to determine the impact on overall respectively disease survival. For this purpose, the pooled hazard ratios (HR) and their 95% confidence intervals (CI) were used for calculation. Twenty-five chemokines were included, and the search revealed 5556 publications. A total of thirty-one publications were included in this systematic review and meta-analysis. Overexpression of chemokine receptor CXCR4 was associated with both a significantly reduced overall survival (HR = 2.70, 95%-CI: 1.57 to 4.66, p = 0.0003) as well as disease-free survival (HR = 2.68, 95%-CI: 1.41 to 5.08, p = 0.0026). All other chemokines showed either heterogeneous results or few studies were available. The overall risk of bias for CXCR4 was rated low. At the current level of evidence, this study demonstrates that CXCR4 overexpression in patients with colorectal cancer is associated with a significantly diminished overall as well as disease-free survival. Summed up, this systematic review and meta-analysis reveals CXCR4 as a promising prognostic biomarker. Nevertheless, more evidence is needed to evaluate CXCR4 and its antagonists serving as new therapeutic targets.